Biocementation of soil using non-sterile enriched urease-producing bacteria from activated sludge - Yang, Yang (2022)
Biocement based on microbially induced carbonate precipitation has become a new construction material for soil cementation. One of the key elements of biocement is urease-producing bacteria (UPB). This paper presents a new method to enrich UPB from waste activated sludge (WAS) under a non-sterile condition so the cultivation of bacteria can be carried out in large-scale for field applications. Using this method, the cost of bacteria cultivation can be reduced by up to 30%. The UPB culture enriched using this method is highly urease active and capable of hydrolyzing urea for calcium carbonate precipitation. After treating sand columns using biocement made of this type of UPB via equal molar cementation solution of 2 M, the unconfined compressive strength of the sand increased to 2.7 MPa and the permeability reduced to a level of 10−6 m/s. These results are comparable with those obtained for biotreatment using pure UPB. Thus, the UPB cultivating method introduced in this paper has the potential to reduce the cost of soil improvement without compromising the performance.